2016
DOI: 10.1007/s12035-016-9719-3
|View full text |Cite
|
Sign up to set email alerts
|

Bergmann Glia, Long-Term Depression, and Autism Spectrum Disorder

Abstract: Bergmann glia (BG), a specific type of radial astrocytes in the cerebellum, play a variety of vital functions in the development of this structure. However, the possible role of BG in the development of abnormalities observed in individuals with autism spectrum disorder (ASD) seems to be underestimated. One of the most consistent findings observed in ASD patients is loss of Purkinje cells (PCs). Such a defect may be caused by dysregulation of glutamate homeostasis, which is maintained mainly by BG. Moreover, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 136 publications
0
16
0
1
Order By: Relevance
“…Together these data indicated that in 16GsoT/T mice, PCs are generated in normal numbers and migrate to their final location, but do not develop normally and are lost as the animals age. This pathology is coupled to abnormalities of the Bergmann glia, the development of which is intimately linked to that of PCs (Chrobak and Soltys 2017; Yamada and Watanabe 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Together these data indicated that in 16GsoT/T mice, PCs are generated in normal numbers and migrate to their final location, but do not develop normally and are lost as the animals age. This pathology is coupled to abnormalities of the Bergmann glia, the development of which is intimately linked to that of PCs (Chrobak and Soltys 2017; Yamada and Watanabe 2002).…”
Section: Resultsmentioning
confidence: 99%
“…In Ngsk Prnp 0/0 mice, GFAP begins to increase gradually from 7 to 8 weeks of age 25 . GFAP is thought to be a significant factor needed for proper communication between Bergmann glia and PC, enabling occurrence of LTD 26 . Indeed, GFAP KO mice exhibited the impairments of cerebellar LTD and eyeblink conditioning 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Another observation in ASD is the loss of Purkinje neuron cells in the cerebellum (Becker & Stoodley, 2013;Kern, 2003;Whitney et al, 2009). Since high extracellular glutamate clearance can lead to neuronal apoptosis (Purcell et al, 2001), disruption of the Bergmann glia, which are radial astrocytes of the cerebellum, may be involved as they are responsible for maintaining extracellular glutamate homeostasis (Chrobak & Soltys, 2017).…”
Section: Neuropathologies With Underlying Functional Astrocytic Changes Regarding Inflammation Transporter Expression Synaptic Regulationmentioning
confidence: 99%